Growth constraints and management consulting: the case of SMEs in peripheral regions. (2018) - Farja, Yanay; Gimmon, Eli; Greenberg, Zeev
This study explores the factors that cause differences in employment growth between young SMEs in core urban and peripheral regions and whether the uneven distribution of resources requires peripheral firms to draw on management consulting to achieve growth. We applied a mixed methods approach that included a quantitative study of 155 Israeli new ventures and ten in-depth interviews with experts from academia and experienced practitioners. Regression analysis results show that management consulting was beneficial for SMEs growth only for those located in peripheral regions. SMEs funded by money from family members grew less than the other firms. The economic development of peripheral areas needs to be carried out by providing potential business owners with two resources that are scarcer in these areas: funding and knowledge.